Exploring the Influence of Signal Molecules on Marine Biofilms Development - Wang, Ruojun; Ding, Wei; Long, Lexin; Lan, Yi; Tong, Haoya; Saha, Subhasish; Wong, Yue Him; Sun, Jin; Li, Yongxin; Zhang, Weipeng; Qian, Pei-Yuan (Frontiers in Microbiology, 2020)
Microbes respond to environmental stimuli through complicated signal transduction systems. In microbial biofilms, because of complex multiple species interactions, signals transduction systems are of an even higher complexity. Here we performed a signal-molecule-treatment experiment to study the role of different signal molecules, including N-hexanoyl-L-homoserine lactone (C6-HSL), N-dodecanoyl-L-homoserine lactone (C12-HSL), Pseudomonas quinolone signal (PQS), and cyclic di-GMP (c-di-GMP), in the development of marine biofilms. Comparative metagenomics suggested the distinctive influence of these molecules on the microbial structure and function of multi-species biofilm communities in the developing stage. The PQS-treated biofilms shared the least similarity with the control and initial biofilms. The role of PQS in biofilm development was further illuminated by a treatment experiment of a single bacterium (Erythrobacter sp. HKB8) isolated from marine biofilms. Comparative transcriptomic analysis showed that 314 genes, such as those related to signal transduction and biofilm formation, were differentially expressed in the untreated and PQS-treated Erythrobacter sp. HKB8 biofilms. Our study demonstrated the different roles of signal molecules in marine biofilm development. In particular, the PQS-based signal transduction system, which is frequently detected in marine biofilms, may play an important role in regulating microbe-microbe interactions and the assemblage of biofilm communities. We presented first-hand evidence and shed new light on the role of signal molecules, especially PQS, in marine biofilm development.